Corrosion of Al0.1CoCrFeNi High Entropy Alloy in a Molten Eutectic Salt. Issue 11 (17th July 2019) - Jalbuena, A. A.; Ury, Nicholas; Bae, Jaewan; Faraj, Christopher; Hanan, Kailey; Kasnakjian, Shahan; Logier, J. K.; Mishra, R. S.; Wang, X.; Earthman, J. C.; Ravi, V.
Abstract : The present work investigates the hot corrosion behavior of Al0.1 CoCrFeNi high entropy alloy (HEA) and Ni-base Alloy 718. Electrochemical tests were conducted to characterize the corrosion behavior of Al0.1 CoCrFeNi HEA and Alloy 718 in a molten Na2 SO4 -NaCl eutectic mixture at 750 ± 5°C in the presence of a platinum catalyzed SO2 /air mixture. The morphology of the surface of Al0.1 CoCrFeNi HEA and Alloy 718 was investigated using scanning electron microscopy (SEM) as well as energy dispersive spectroscopy (EDS). The results indicate that the polarization resistance of the HEA was higher and the corrosion rate lower in comparison with Alloy 718. SEM and EDS analyses reveal the formation of a dual oxide layer on the HEA that provides a better corrosion barrier compared to the single chromia scale observed on Alloy 718.